2.5 D carbon/carbon composites modified by in situ grown hafnium carbide nanowires for enhanced electromagnetic shielding properties and oxidation resistance. (May 2020) - Tian, Song; Zhou, Lu; Liang, Zhongtian; Yang, Yu; Wang, Yanru; Qiang, Xinfa; Huang, Shilin; Li, Haojie; Feng, Shi; Qian, Zhonghao; Zhang, Yangbo
Abstract: Hafnium carbide nanowires (HfCnw) were in-situ grown in 2.5 D needle-punched carbon felts by a catalyst-assisted chemical vapor deposition method. Subsequently, the carbon felts were densified to obtain HfCnw reinforced carbon/carbon (HfCnw-C/C) composites via chemical vapor infiltration. Effects of HfCnw on electrical conductivity, electromagnetic shielding properties and oxidation resistance of C/C composites were investigated for the first time. The results show that the SET of C/C composites with 1.75 wt % HfCnw exceeds 40 dB in the whole frequency range of 8.2–12.4 GHz, implying more than 99.99% of the incident beam was shielded. Moreover, it is found that the relative magnitude relationship of the total shielding effectiveness of composites (SET(S-2h)  > SET(S-3h) > SET(S-0h) ) is similar with the conductance ( σ S-2h > σ S-3h > σ S-0h ), which indicates the conductance can effectively predict the relative magnitude of the SET . In addition, the analysis based on oxidation curves demonstrates that HfCnw significantly enhance the oxidation resistance of the composites even with a small amount of HfCnw. The high electromagnetic interference (EMI) shielding effectiveness coupled with relatively low density and good oxidation resistance of HfCnw-C/C composites make itself exhibit remarkable potential as lightweight and high-performance structural-functional integrated materials for future EMI shielding application. Graphical abstract: Image 1075 Highlights: Electromagnetic shielding properties and oxidation resistance of HfCnw-C/C composites were investigated for the first time. The SET of 1.75 wt.% HfCnw-C/C composites exceeds 40 dB in the X-band; > 99.99% of incident beam was shielded. Current HfCnw-C/C composites have relatively low density, high EMI SE and good oxidation resistance.